2015
DOI: 10.18632/oncotarget.4755
|View full text |Cite|
|
Sign up to set email alerts
|

Bisphosphonate-induced differential modulation of immune cell function in gingiva and bone marrowin vivo: Role in osteoclast-mediated NK cell activation

Abstract: The aim of this study is to establish osteoclasts as key immune effectors capable of activating the function of Natural Killer (NK) cells, and expanding their numbers, and to determine in vivo and in vitro effect of bisphosphonates (BPs) during NK cell interaction with osteoclasts and on systemic and local immune function. The profiles of 27 cytokines, chemokines and growth factors released from osteoclasts were found to be different from dendritic cells and M1 macrophages but resembling to untreated monocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 46 publications
5
59
0
Order By: Relevance
“…The multiplex assay of cultured oral barrier cells suggested the significant reduction in secretion of cytokines and chemokines in the ZOL group at week 2 ( Fig. 2C), which was consistent with the previously reported microarraybased transcriptome assay of the mouse oral barrier tissue (50). The oral barrier microenvironment of ZOL mice may be less effective for wound healing and inflammatory resolution.…”
Section: Ly6gsupporting
confidence: 89%
See 3 more Smart Citations
“…The multiplex assay of cultured oral barrier cells suggested the significant reduction in secretion of cytokines and chemokines in the ZOL group at week 2 ( Fig. 2C), which was consistent with the previously reported microarraybased transcriptome assay of the mouse oral barrier tissue (50). The oral barrier microenvironment of ZOL mice may be less effective for wound healing and inflammatory resolution.…”
Section: Ly6gsupporting
confidence: 89%
“…We previously reported that bisphosphonate-affected osteoclasts secreted proinflammatory cytokines (50), which appeared to locate adjacent to the osteonecrosis area (31) (Fig. 1).…”
Section: Ly6gmentioning
confidence: 81%
See 2 more Smart Citations
“…We have previously shown that this myeloid subset is a potent activator of NK cells, and their effect on the induction of cytotoxicity and secretion of cytokines and chemokines by NK cells is much stronger than when using monocytes or DCs [62]. Human osteoclasts produce IL-15, IL-12, IL-18 and IFN-α, but not IFN-γ; they express low levels of MHC class I and II, CD14, CD11b and CD54, and they do not upregulate MHC class I surface expression when treated with either the combination of TNF-α and IFN-γ or with activated NK supernatants known to increase MHC class I expression [62]. Low expression of MHC class I together with increased release of IL-15, IL-12, IL-18 and IFN-α may be the main mechanisms by which osteoclasts are able to expand functionally potent NK cells ([62], manuscript in preparation).…”
Section: Adoptive Transfer Of Ex Vivo Osteoclast-expanded Nk Cells Elmentioning
confidence: 99%